Does the Specialist Matter? Differential Execution Costs and Intersecurity Subsidization on the New York Stock Exchange. - Cao, Charles; Choe, Hyuk; Hatheway, Frank (Journal of Finance, 1997)
This article tests for differences in execution costs among specialist firms for New York Stock Exchange listed securities. Execution cost differences provide a measure of the relative performance of specialist firms. The authors find a substantial difference in effective spreads and order processing costs across specialist firms, controlling for stock characteristics. While economically significant, the differences in execution costs between specialist firms are much smaller than the cross-market differences reported by Roger Huang and Hans Stoll (1996). Within a specialist firm, there is a positive relation between order processing costs and trading activity that is consistent with the hypothesis that active stocks subsidize inactive stocks.